3(x+4)-4=2(x+4

Simple and best practice solution for 3(x+4)-4=2(x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+4)-4=2(x+4 equation:



3(x+4)-4=2(x+4
We move all terms to the left:
3(x+4)-4-(2(x+4)=0
We multiply parentheses
3x-(2(x+4)-4+12=0

See similar equations:

| 12x+15=7x8 | | -6+1/2x=-9/2 | | 5x+11=3x-2 | | 15-3x2=0 | | 2(3x+9)=-2(2x+6 | | x3/2−8=0 | | 2x-10=-x-37 | | 21=4/5x | | -3(x+4)+5(3-2x)=2(x-1)-4(3-2x) | | (d/36)-(d/45)=17/60 | | 6-7c=3(2c+1) | | 3x-18=8x=14x+7 | | 4m+6=-(2-3m) | | 14=14+3x/2 | | -4x=3(-3x-2)+59 | | |16x+27|=27 | | 6x+7x=75 | | 25+x=-30 | | 3r+9r+(12-2r)=26 | | g/9+29=36 | | f/10+32=33 | | 9+3g=15 | | 7x-3-2x-27=5x-6-3x | | -7.8-6.9=v+6.3 | | 60*0.10x=105 | | -3x+6=2x+5=6 | | 4|-4x-5|-8=20 | | 120+6x/6=6x | | 33.3(6x-9=-33 | | 38t-12=6(t-1)4 | | X-4x=6x+9-8x | | 7x-3-2x-27=5x-6 |

Equations solver categories